The Sensory Sensitivity of Blind People in Creating the Convenience Concept in their House Interior - Mahdi Nurcahyo (Institut Seni Indonesia Surakarta, 2020)
This study aims to examine how a blind person recognizes and presents the aspects of convenience inside the house. The limited ability to see does not make the blind people weak, but it becomes an advantage and an easy walk when carrying out daily activities at home. The experience of the body and senses of the occupied space opens the blind people's awareness to be able to create a